Managing vulnerability: cross-sector reflections on the ethics and equity implications of AI use among young adults with chronic conditions - MacKenzie Isaac; Sneha Dave; Terry Adirim (Frontiers in Digital Health, 2026)
Generation Patient, a global advocacy organization led by young adults with chronic and rare medical conditions, convened a Roundtable in December 2025 to explore the potential and realized impacts of increased AI use in patient care. Across two hours, fifteen participants with a blend of lived, scholarly, and professional expertise engaged in a semi-structured focus group on the benefits and drawbacks of using AI to meet their healthcare needs within and beyond the clinic. Reflexive thematic analysis of the Roundtable transcript shed light on AI's promise to ease the administrative and emotional burden for young adults with complex conditions transitioning into adult care. However, increased use of AI for clinical administrative support raises concerns about patient data protection, stewardship, and equity. The Roundtable also extensively discussed the “double edged sword” of generative and conversational AI's tendency to affirm users' inputs, particularly in the case of mental health companion chatbots. Committed to translating these insights into actionable steps, participants recommended that AI developers and distributors adopt a DesignJustice approach—modeled by the Roundtable itself—to collaboratively build AI tools with end users and health equity experts who can support the creation of ethical standards, marketing strategies, and impact evaluations that focus on reducing harm and maximizing social good. At a policy level, broadening definitions of what constitutes a “medical device” to any AI tool with the capability of processing health-related data will increase the scope of the federal government's obligation and ability to protect patients.